2019
DOI: 10.4103/apc.apc_47_18
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio used as prognostic factor marker for dilated cardiomyopathy in childhood and adolescence

Abstract: Objective:The objective of this study is to evaluate the neutrophil-to-lymphocyte ratio (NLR) and platelet–lymphocyte ratio, from the hemograms obtained from children and adolescents with dilated cardiomyopathy (DCM), and to correlate them with the levels of B-type natriuretic peptide (BNP) and with the clinical evolution of these patients in the long term.Materials and Methods:Follow-up of 57 patients with DCM was made retrospectively, with hemogram and BNP level determination being performed after optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…C-reactive protein is a nonspecific biomarker of inflammation and a well-known causative factor of endothelial dysfunction [ 11 ]. As observed in other chronic diseases, such as systemic arterial hypertension, diabetes, cancer or chronic kidney disease, the inflammatory process is also observed in heart failure [ 12 , 13 ]. Studies have shown that patients with chronic heart failure (CHF), regardless of the etiology, have elevated serum levels of hs-CRP [ 14 , 15 , 16 ].…”
Section: Inflammatory Biomarkersmentioning
confidence: 98%
See 3 more Smart Citations
“…C-reactive protein is a nonspecific biomarker of inflammation and a well-known causative factor of endothelial dysfunction [ 11 ]. As observed in other chronic diseases, such as systemic arterial hypertension, diabetes, cancer or chronic kidney disease, the inflammatory process is also observed in heart failure [ 12 , 13 ]. Studies have shown that patients with chronic heart failure (CHF), regardless of the etiology, have elevated serum levels of hs-CRP [ 14 , 15 , 16 ].…”
Section: Inflammatory Biomarkersmentioning
confidence: 98%
“…Additionally, patients with heart failure and elevated white blood cell count, neutrophilia and lymphocytopenia, have an increased mortality [ 22 , 23 ]. The neutrophil to lymphocyte ratio has recently emerged as a new inflammatory biomarker that can be used in the staging prognosis of several chronic diseases [ 12 , 24 ]. Thus, in the last few years, NLR has been shown to be an eligible biomarker associated with the severity of chronic heart failure in children, adolescents [ 12 ] and adults with dilated cardiomyopathy [ 22 ].…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Bu iki belirtecin akut ve kronik inflamasyon ile ilişkili jinekolojik, gastrointestinal ve kardiyak patolojileri içeren birçok durumda faydalı olduğu gösterilmiştir. [12][13][14][15] Bu çalışmanın amacı, bahsedilen bu yeni iki belirtecin inflamatuar sürecin önemli rol oynadığı düşünülen AI olgularında tanısal değerlerini incelemek ve gebelik sonuçlarını öngörmedeki yerini araştırmaktır.…”
Section: Introductionunclassified